Failure Analyse Prediction of Bolts Component Using Probality Method - F. R. M., Romlay; M. E., Wahab; M. I. A., Halim; M. H. M., Saad (Universiti Malaysia Pahang, 2008)
In a chemical factory there are steam pipes, which convey high pressure and high temperature steam, sealed with end flanges by 12 bolts at each end. Several bolts at the end of the flange were broken suddenly during the maintenance work. The investigation was performed to predict the failure of the bolt. Stress, strain and deformation of the bolts were analyzed. From the simulation, the failure happened almost close to the end of the bolt where it had been fixed. The simulation result was validated by the results that were produced by probability method. The failure may be prevented by using the right material with a large diameter or by changing the design of the bolt.